New business ventures and the entrepreneur (McGraw-Hill, 2007)
New Business Ventures, 6e will leave students with the skills needed to grasp and implement the general managerial responsibilities required to be a successful entrepreneur. The text provides an innovative approach to teaching the core general management skills via the lens of the entrepreneur. The course upon which this book I based is now the new core required course in general management at Harvard Business School